2012
DOI: 10.1111/j.1096-0031.2012.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Mazaedium evolution in the Ascomycota (Fungi) and the classification of mazaediate groups of formerly unclear relationship

Abstract: Calicioid or mazaediate fungi constitute a heterogeneous assemblage of fungi sharing the presence of a mazaedium. These fungi were once treated as an order (Caliciales) of the Ascomycota but many are now known to be nested within the Arthoniomycetes, Eurotiomycetes, Lecanoromycetes and Leotiomycetes. In this study we employ multigene phylogenetic analyses of main mazaediate groups (based on nuclear 18S, 28S, 5.8S rDNA, mitochondrial 16S, and the protein coding RPB1 and Mcm7) of 116 taxa corresponding to most m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 98 publications
2
61
0
Order By: Relevance
“…Recent research on the evolution of the mazaedium, a type of passively spore-dispersion structure, confirmed that the genus Caliciopsis Peck (Coryneliales, Ascomycota) belongs to the Eurotiomycetes (Prieto et al 2013). This was previously suggested in several comprehensive phylogenetic studies (Geiser et al 2006;Spatafora et al 2006).…”
Section: Introductionmentioning
confidence: 68%
“…Recent research on the evolution of the mazaedium, a type of passively spore-dispersion structure, confirmed that the genus Caliciopsis Peck (Coryneliales, Ascomycota) belongs to the Eurotiomycetes (Prieto et al 2013). This was previously suggested in several comprehensive phylogenetic studies (Geiser et al 2006;Spatafora et al 2006).…”
Section: Introductionmentioning
confidence: 68%
“…2), but never with bootstrap support above 70%. Previous large-scale phylogenies for the Lecanoromycetes show support for two contradicting relationships among these three subclasses: a sister relationship between the Ostropomycetidae and Umbilicariomycetideae (PP = 0.98 in Lutzoni et al, 2004, for the phylogeny based on three genes), and between the Lecanoromycetidae and Ostropomycetidae (PP = 1.00 and ML-BP = 80% in Bendiksby and Timdal, 2013; and PP = 0.99 in Prieto et al, 2012). The recognition of the Umbilicariomycetidae as a separate subclass enables the tracking of this phylogenetic uncertainty.…”
Section: Resultsmentioning
confidence: 98%
“…In Wedin et al (2005) the Acarosporomycetidae and paraphyletic ‘Candelariomycetidae’ (sensu Bendiksby and Timdal, 2013) form a monophyletic group closely related to the outgoup taxa (Eurotiomycetes; however, without support). Most recently, Prieto et al (2012) presented a Bayesian tree based on four ribosomal and two protein-coding genes ( MCM7 and RPB1 ) where Candelariales is separated from the Lecanoromycetes and placed as an independent lineage among early diverging Leotiomyceta. However, this placement, as well as many other deep phylogenetic relationships associated with the Leotiomyceta radiation, did not receive strong support (Lutzoni et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Further, morphological and chemical features have also been shown to be highly plastic in other groups of lichenized fungi (e.g. Caliciales, Prieto et al 2013;Cladoniaceae, Parnmen et al 2010;Collemataceae, Otálora et al 2013;Graphidaceae, Rivas Plata & Lumbsch 2011;Roccellaceae, Tehler & Irestedt 2007). Therefore, it is not surprising that the monophyly of Canoparmelia based on phenotypic feature was not recovered in our molecular phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 99%